PDE4B promotes JNK/NLRP3 activation in the nucleus pulposus and mediates intervertebral disc degeneration - Weixing Xu; Rana Dhar; Kaiyue Li; Danyang Zheng; Minxin He; Weiguo Ding; Long Xin; Bin Xu; Yuqing He; Qi Peng; Huifang Tang (Scientific Reports)
Abstract Intervertebral disc degeneration disease (IDD) is one of the leading causes of disability, and current therapies are ineffective. Phosphodiesterase 4B (PDE4B) plays essential roles in regulating the activation of the NLRP3 inflammasome. However, whether PDE4B or NLRP3 is involved in the development of IDD is unclear. This study sought to explore the role of PDE4B in IDD pathogenesis by in vivo and in vitro experiments. This results showed that PDE4B and NLRP3 were significantly upregulated in nucleus pulposus (NP) tissues from IDD-related human patients. Deletion of PDE4B in the NP resulted in downregulated JNK and NLRP3. Aberrant PDE4B expression enhanced the phosphorylation of JNK and NLRP3 expression. Furthermore, genetic ablation of the pde4b gene delayed IDD pathogenesis, and PDE4 inhibitor also can reverse the IDD pathogenesis. Our study showed that aberrant PDE4B activation in NP tissues induces pathological changes in IDD, phosphorylation of JNK and NLRP3 are involved in this process, and inhibition of aberrant PDE4B activity is a potential therapeutic strategy for IDD.